(3eYGgO GdJfUjU Ydi ThGgO GdJdNjUs - (3YHO GdQMje GdYHGSs; (3eMeO Hf YHO GdQMef Hf YeQ, CHh GdeYGdj, LdGd GdOjf GdbRhjfj GdTGaYj, GdeYQha HNWjH OeTb,J (B739 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdabjQ s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B145s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B477s
Keywords: (3GdHdGZIs